A Comparative Study Between Pomodoro and Flowtime Techniques Among College Students - Renacido, John Marvin D.; Mayordo, Emmanuel L.; Biray, Ersyl T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This mixed-method study compared the efficacy of Pomodoro and Flowtime study techniques as described by students in a state university. Quantitative data were gathered from 108 respondents, while the qualitative data were supplied by 12 participants through a virtual interview. Results revealed that the majority of the respondents preferred the Pomodoro technique for its structured intervals, stress-reducing breaks, and productivity tracking, with its rigid scheduling noted as a limitation; a minority favored the Flowtime technique for its immersive focus and task engagement, yet less effectiveness when motivation was low. Quantitative data support that the Pomodoro technique is more effective than the Flowtime technique in terms of memory retention, academic performance, and time management. Conversely, Pomodoro is less effective in terms of focus, flexibility, and motivation. Qualitative analysis, however, revealed that the Pomodoro technique is effective in structured environments, especially for those who need uninterrupted focus, even if the Flowtime technique proves its efficacy for deep work and creativity, except in less controlled environments.